Strategi Pemasaran Olahan Kedelai Menjadi Tahu Dan Tempe Di Kecamatan Gondang Kabupaten Tulungagung - Faisal, Herry Nur (Universitas Islam Kadiri, 2024)
This research aims to identify internal, external and strategic factors in marketing Tofu and Tempeh in Gondang District, Tulungagung Regency. Determination of informants in this research was carried out using proportional random sampling. The informants in this research were divided into 15 tofu entrepreneurs and 15 tempeh entrepreneurs. Data analysis uses SWOT analysis. The results of the research show that the factors contained in the marketing of tofu and tempe businesses in Gondang District are internal factors and external factors. From the results of identifying internal factors, there are strengths and weaknesses. The strength of the tofu and tempeh marketing strategy in Gondang District is the use of technology in production, processing tofu and tempeh waste, tofu and tempeh products, favorite foods for all groups. The weaknesses are lack of workforce skills and innovation, simple packaging form, lack of promotional activities. From the results of identifying external factors, there are opportunities and threats. Opportunities in the tofu and tempeh marketing strategy in Gondang District are that there is still a lot of demand for tofu and tempeh, there are still many trading centers, close to the trading center. Meanwhile, the threat is: demand for products decreases if the price of chicken and fish is cheap, the price of raw materials for soybeans is unstable. From the results of the discussion, the strategy applied in marketing tofu and tempeh in Gondang District is 1) Keeping raw materials available 2) Improving product quality so that it has characteristics its own specialty 3) Improving the quality of product packaging 4) Expanding marketing channels by utilizing good cooperative relationships with distributors and adding promotional activities when selling via social media so that consumers are not lost 5) improving the quality of tofu and tempeh to compete with animal protein such as fish and chicken meat